Advancements in Ore Beneficiation Technologies: A Review of Modern Extraction Methods - Gaurav Jaiswal (International Journal of Minerals, 2025)
Ore beneficiation plays an essential role in the mining industry, as it facilitates the extraction of valuable minerals from their ores while ensuring maximum efficiency and minimal environmental impact. Beneficiation technologies have evolved significantly over time, leading to improvements in metal recovery rates and reduced waste generation. These advancements have enabled the mining industry to address increasing resource demands, with a particular focus on sustainability and cost-effectiveness. In this review, we explore the latest developments in ore beneficiation methods, emphasizing the innovations, technological advancements, and ongoing challenges in the extraction of high-quality minerals. The paper presents an overview of conventional beneficiation techniques, such as flotation, magnetic separation, and gravity separation, all of which continue to serve as the cornerstone of mineral processing. Additionally, the review highlights modern technologies that have emerged to enhance ore beneficiation efficiency. Bioleaching, a biologically-driven method, has gained attention due to its environmentally friendly characteristics, while advancements in gravity separation have allowed for the processing of finer ores with higher precision. Furthermore, high-efficiency processing technologies, such as sensor-based sorting and hydrometallurgical techniques, have led to improvements in ore grade and recovery. Despite the promise of these advanced methods, the review also discusses the challenges faced by the industry, including the processing of complex ores, water and energy consumption, and the economic feasibility of implementing cutting-edge technologies at scale. This paper offers a comprehensive analysis of both traditional and modern ore beneficiation technologies, underscoring the importance of ongoing research and innovation in overcoming these challenges and meeting the growing global demand for metals and minerals.
Keywords: Ore beneficiation; bioleaching; flotation; gravity separation; hydrometallurgy; magnetic separation; sensor-based sorting; sustainable mining